Laser altimeter data obtained over sea-ice during the GreenIce campaign in May, 2004; profile GreenICE2004_SBLA_20040513T1909_85.68_-72.12_thr06_data_Vers5 - Hendricks, Stefan; Haas, Christian; Krumpen, Thomas (In: Hendricks, S et al. (2024): Laser altimeter data obtained over sea-ice during the GreenIce campaign in May, 2004 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.970485, 2024)
Sea ice surface roughness data were obtained during the GreenIce campaign in May, 2004 with a Single Beam Laser Altimeter (SBLA) mounted inside an electromagnetic system (EM-Bird) towed at 10-30 m height above surface by a Helicopter (Unknown model). A method developed by Hibler (1972) was used to a) isolate the surface profile from low-frequency variations associated with the aircraft motion and b) to identify pressure ridge sails. The processing steps are described in https://epic.awi.de/id/eprint/56364/. We applied a ridge detection threshold of 0.6 m, which means that only sails higher 0.6 m are detected. Version and name of the processing routine: Laser_Altimeter_Processing_VS5_06_20.py (vers.5, Feb 22, 2024, https://gitlab.awi.de/sitem/sbla_processing.git). SBLA records (RIEGL - LD90) are provided at a sampling rate of 100 Hz. Sensor accuracy is 5 cm with a beam diameter at surface of 5.8 cm. This specific dataset was obtained on 20040513T1909. It includes recorded altimeter readings, the derived surface elevation and width/height/spacing of detected pressure ridge sails. Note on data quality: 5.8 cm . File name: [DMS/PANGAEA Campaing Identifier] + [DEVICE] + [DATE/TIME] + [LAT/LON] + [Detection Threshold] + [Object] + [Version] + [Format]
Keywords: Laser Altimeter; Ridge Height; Ridge Spacing; Ridge Width; Sea Ice Surface Roughness